2009
DOI: 10.1016/j.jmp.2009.06.004
|View full text |Cite
|
Sign up to set email alerts
|

A model of the emergence and evolution of integrated worldviews

Abstract: It is proposed that the ability of humans to flourish in diverse environments and evolve complex cultures reflects the following two underlying cognitive transitions. The transition from the coarse-grained associative memory of Homo habilis to the fine-grained memory of Homo erectus enabled limited representational redescription of perceptually similar episodes, abstraction, and analytic thought, the last of which is modeled as the formation of states and of lattices of properties and contexts for concepts. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
3
2

Relationship

4
4

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 68 publications
0
44
0
Order By: Relevance
“…The ill-defined idea can be said to be in a 'state of potentiality' because it could actualize different days depending on the different perspectives or contextual cues taken into account as it takes shape. Honing theory is derived from the notion that individuals' internal models of the world, or worldviews, self-organize to achieve a more stable equilibrium state [31,32,44]. Creative outputs are viewed as the external byproducts of this internal, transformative, entropyminimizing process; thus the theory is consistent with the therapeutic nature of the creativity [48].…”
Section: An Evolutionary Framework For Creativity?mentioning
confidence: 99%
See 2 more Smart Citations
“…The ill-defined idea can be said to be in a 'state of potentiality' because it could actualize different days depending on the different perspectives or contextual cues taken into account as it takes shape. Honing theory is derived from the notion that individuals' internal models of the world, or worldviews, self-organize to achieve a more stable equilibrium state [31,32,44]. Creative outputs are viewed as the external byproducts of this internal, transformative, entropyminimizing process; thus the theory is consistent with the therapeutic nature of the creativity [48].…”
Section: An Evolutionary Framework For Creativity?mentioning
confidence: 99%
“…So long as exposure to highly similar items or events causes the formation of abstract concepts that connect these instances, an associative memory that meets certain criteria is expected, sooner or later, to reach a critical percolation threshold such that the number of ways of forging associations amongst items in memory increases exponentially faster than the number of items in memory. This is an entropy-minimizing process and the outcome is that the worldview achieves a more stable equilibrium state that (following Kauffman's use of the term 'autocatalytic closure') has been referred to as conceptual closure [31,32,44].…”
Section: Applying Communal Exchange To Cultural Evolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though the basic idea of framing creativity in evolutionary terms is promising, the authors' proposal to model creativity as a Darwinian process of trial and error presents theoretical problems, and their suggested implementation using a Bayesian network is not sufficiently fleshed out to enable evaluation. An alternative is to model the evolution of creative ideas as a Lamarckian process, drawing on formal models of concept combination (which lends itself to mathematical modeling more readily than some other creative processes) (e.g., Aerts & Gabora, 2005;Gabora, 2013;Gabora & Aerts 2009). The approach addresses the challenge of modeling the emergence of new attributes (such as emergence of the concept of a spout during the invention of a teapot) (Gabora, & Carbert, 2015;Gabora, Scott, & Kauffman, 2013).…”
Section: A Path Forwardmentioning
confidence: 99%
“…The last two decades have witnessed an explosion of applications of quantum models to psychological phenomena that feature ambiguity and/or contextuality [2][3][4]. Many psychological phenomena have been studied using quantum models, including the combination of words and concepts [5][6][7][8][9][10], similarity and memory [11,12], information retrieval [13,14], decision making and probability judgment errors [15][16][17][18][19], vision [20,21], sensation-perception [22], social science [23,24], cultural evolution [25,26], and creativity [27,28]. These quantum inspired approaches make no assumption that phenomena at the quantum level affect the brain, but rather, draw solely on abstract formal structures that, as it happens, found their first application in quantum mechanics.…”
Section: Introductionmentioning
confidence: 99%